A sustainable approach for developing biocarbon from lignin and its utilization in recycled ocean nylon based biocomposites - Zohrah B. Varsally; Neelima Tripathi; Haftom Weldekidan; Arturo Rodriguez-Uribe; Oisik Das; Amar K. Mohanty; Manjusri Misra (Composites Part C: Open Access, 2023)
Nylon/polyamide (PA6) is a major cause of ocean plastic pollution because of its extended use in commercial fishing activities. Recovery of this nylon from oceans and its use in manufacturing new materials or composites is urgently required to promote sustainability and circularity. In this work, unlike higher-density mineral fillers, lignin from the forestry industry was converted into biocarbon, which was used as a lightweight filler to manufacture recycled-ocean nylon (RN)-based composites. Biocarbon is a highly stable, competitive, and sustainable filler for high-performance engineering plastics such as nylon. Lignin was pyrolyzed at 600 °C followed by further treatment at 1200 °C (with and without cobalt (II) nitrate catalyst) to induce graphitization in the produced biocarbon. Among the three types of biocarbon samples, such as pyrolyzed at 600 °C, 1200 °C and 1200 °C catalyzed lignin biocarbon, the catalyzed biocarbon showed the maximum electrical conductivity. Catalyzed lignin biocarbon pyrolyzed at 1200 °C showed an increase of 85% in electrical conductivity compared to commercial mineral graphite. The biocomposites consisting of 600 °C biocarbon were manufactured by injection molding at different filler contents up to 40 wt.%. The biocomposites consisting of 40% of pyrolyzed lignin at 600 °C showed increased flexural strength, flexural modulus, and heat deflection temperature by 41, 76 and 76%, respectively, compared to neat RN. Improved properties of the prepared biocarbons and biocomposites showed the potential of RN-based composites in the automotive industries.